The Appeal of Influencers to the Social Media Outreach of Indian Politicians - Lalani, Faisal; KM, Ramaravind; Pal, Joyojeet (Computer Supported Collaborative Work, 2019)
Democracies around the world have different levels of dependence on influencers outside of mainstream politics in their outreach efforts. In this study, we examine the case of India, specifically the relationship between politicians in power and “influencers”, such as celebrities and media accounts, they follow on Twitter. We find that while politicians engage with these accounts to the same degree to which they follow them, the media accounts at the highest levels of engagement share the same ideology as the politicians who follow them. No similar alignment exists between celebrities and politicians, which requires future work of analyzing the content of engaging tweets in order to define the extent to which these accounts have political influence.